A Conceptual Framework of Arabic Reading Skills in Qurâ€™anic Memorization: Integrating Philosophy of Science and AI-Assisted Learning - Riza Egy Ramadhani; Oktavia Ratnaningtyas; M. Yunus Abu Bakar; Tharwah Attia (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
This study addresses the tendency in Qur’anic learning research to separate reading skills (maharah qira’ah) and memorization, without integrating them within a philosophy of science framework. In addition, the use of Artificial Intelligence (AI) remains largely technical. This study aims to construct a conceptual framework integrating reading and memorization from ontological, epistemological, and axiological perspectives, and to explore AI-assisted learning as a supporting approach. A qualitative systematic literature-based conceptual design was employed using thematic analysis and conceptual synthesis. The findings indicate that reading functions ontologically as a meaning-making process, epistemologically as a mechanism of knowledge construction through encoding, storage, and retrieval, and axiologically as a means to improve memorization quality in terms of accuracy, retention, and efficiency. AI integration strengthens these processes through real-time feedback and adaptive learning, enabling an integrated learning cycle between reading and memorization. This study contributes a conceptual framework linking reading, memorization, and technology within a unified epistemic system